A Method for Identifying Factual Corruption of the Navigation Signal and Identifying the Interference Influence on Unmanned Aerial Vehicle Receiver - Linets,Gennady (2021)
ABSTRACT Objectives of this article are to create a method that should identify distortion of navigation signals using supplementary information obtained whilst processing the navigation parameters in the calculator of the navigation receiver. To develop this method, a comparative evaluation of the actual data of the navigation measurements with the calculated data values and a Bayesian probabilistic approach for detecting the navigation field distortion and identifying the interference. Test of results of the developed method showed that it enables a highly reliable assessment of the state of the navigation field and, if distorted, the identification of the distortion type: normal (undistorted) condition; abnormal state: when abnormally high errors appear spasmodically in the positioning estimation within individual measuring channels of the navigation receiver; slightly distorted state leading to a slow change in positioning accuracy; active spoofing manifested in the substitution of positioning coordinates. The article provides a new method for processing navigation parameters allowing to detect the fact of the navigation fields (NF) distortion and identify the interference effect on the navigation receiver (NR) of UAV.